2017
DOI: 10.1536/ihj.16-461
|View full text |Cite
|
Sign up to set email alerts
|

Young Paradoxical Stroke Treated Successfully with Mechanical Thrombectomy Using Solitaire and Transcatheter Closure of Patent Foramen Oval

Abstract: SummaryParadoxical embolization is the mechanism for patent foramen ovale (PFO)-associated cryptogenic stroke and transcatheter closure of PFO may prevent recurrent ischemic stroke. Mechanical thrombectomy is promising to treat acute ischemic stroke due to high rates of reperfusion and reduced intracranial hemorrhage complications. We report the case of a 27-year-old woman with a massive cerebral infarction but no evidence for any atherosclerosis, who received an urgent mechanical thrombectomy with a Solitaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(20 reference statements)
0
1
0
Order By: Relevance
“… 12 , 13) Another study demonstrated the efficacy of transcatheter PFO closure after achieving recanalization by mechanical thrombectomy in a young patient with cryptogenic stroke and PFO without PE. 14) Transcatheter PFO closure could be offered for patients at high risk of a recurrent embolic event, such as patients with atrial septal aneurysm, a long PFO tunnel, or a substantial right-to-left shunt. 15) Therefore, we recommend not only requiring rehabilitation for stroke but also considering PFO closure.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13) Another study demonstrated the efficacy of transcatheter PFO closure after achieving recanalization by mechanical thrombectomy in a young patient with cryptogenic stroke and PFO without PE. 14) Transcatheter PFO closure could be offered for patients at high risk of a recurrent embolic event, such as patients with atrial septal aneurysm, a long PFO tunnel, or a substantial right-to-left shunt. 15) Therefore, we recommend not only requiring rehabilitation for stroke but also considering PFO closure.…”
Section: Discussionmentioning
confidence: 99%